Self-Esteem as a Mediator Between Peer Victimization and Social Withdrawal in Youth - Chaiyasit, Kittipong; Sari, Intan; Gong, Jiaowei (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to examine whether self-esteem mediates the relationship between peer victimization and social withdrawal in adolescents. Methods and Materials: A descriptive correlational research design was employed involving a sample of 329 Indonesian adolescents aged 12–18 years, selected using the Krejcie and Morgan (1970) sample size determination table. Participants completed standardized self-report instruments: the Revised Peer Experiences Questionnaire (RPEQ) to assess peer victimization, the Rosenberg Self-Esteem Scale (RSES) for self-esteem, and the Withdrawn/Depressed subscale of the Child Behavior Checklist (CBCL) to measure social withdrawal. Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlation, while Structural Equation Modeling (SEM) was conducted using AMOS-21 to test direct, indirect, and total effects among variables. Model fit indices were computed to assess structural validity. Findings: Descriptive analyses indicated moderate levels of peer victimization (M = 48.72, SD = 9.84), self-esteem (M = 27.45, SD = 4.93), and social withdrawal (M = 15.83, SD = 5.41). Pearson correlations showed significant associations among all variables: peer victimization was negatively correlated with self-esteem (r = -0.47, p < .001) and positively with social withdrawal (r = 0.53, p < .001), while self-esteem was negatively associated with social withdrawal (r = -0.42, p < .001). The SEM results supported a partial mediation model with good fit indices (χ²/df = 1.96; CFI = 0.97; RMSEA = 0.052). Self-esteem significantly mediated the effect of peer victimization on social withdrawal (indirect β = 0.14, p < .01), indicating that low self-esteem partially explains the link between victimization and withdrawal behavior. Conclusion: This study highlights the critical mediating role of self-esteem in the association between peer victimization and social withdrawal among adolescents. Interventions aimed at strengthening self-esteem may serve as effective buffers to reduce withdrawal behaviors in victimized youth.